Excel 2016 Power Programming with VBA - Alexander, Michael 1972-; Kusleika, Dick (John Wiley & Sons, Inc., 2016)
Excel 2016 Power Programming with VBA is fully updated to cover all the latest tools and tricks of Excel 2016. Encompassing an analysis of Excel application development and a complete introduction to Visual Basic for Applications (VBA), this comprehensive book presents all of the techniques you need to develop both large and small Excel applications. Over 800 pages of tips, tricks, and best practices shed light on key topics, such as the Excel interface, file formats, enhanced interactivity with other Office applications, and improved collaboration features. In addition to the procedures, tips, and ideas that will expand your capabilities, this resource provides you with access to over 100 online example Excel workbooks and the Power Utility Pak, found on the Mr. Spreadsheet website.